(untitled) - Fellag, Linda Robinson (New York, 2006)
This book includes: Ten thematic units to develop academic skills in English while building test-taking confidence; Integrated skill practice to develop critical thinking and communicative competence; Authentic TOEFL® iBT practice sets created by ETS especially for this series; Practical tips to sharpen test-taking strategies; Teacher's Manuals with evaluation tools to track students' progress and actual student responses (speaking and writing) at all score levels.
Keywords: English language,English language,Test of English as a foreign language; Examinations